Condições de vida e hábitos culturais em saúde em comunidade tradicional do Baixo Amazonas: o caso do quilombo/mocambo Muratubinha - PONTES, Deize Freitas (Universidade Federal do Oeste do Pará, 2021)
This dissertation focuses on the way of life and cultural habits with regards to the population in Amazonian region, highlighting a Remnant Community of Quilombos (Black) Muratubinha, in western of Pará, characterized by its environmental diversity, socio-cultural complexities and geographical conditions. The scientific question that guided the research is: do daily social practices and cultural health habits influence the quality of life of the quilombo community residents in the Amazon region? The research aimed to investigate the living social conditions and cultural practices of quilombos with health disease process, showing or not points that link the cultures of the investigated community residents, the environment in which they live and how the collective health is promoted by and among the population, in addition to the associated aspects that interfere with the health and resources used by quilombos, in a preventive and curative manner. The qualitative approach research with ethnographic method elements focused on a community of remnants of quilombos, Muratubinha, characterized as lowland, in Óbidos-PA. Through a questionnaire application with semi-structured interviews with key-narrators and participant observation, transcription and analysis of information, the results were validated, enabling a scientific and citizenship positioning of living and health conditions of community, identifying and empowering the quilombo culture in the maintenance of its identity and knowledge.